Effect of the Fineness of Artificial Pozzolana (Sarooj) on the Properties of Lime-Pozzolana Mixes - Abdel Wahid Hago; Amer Ali Al-Rawas; Awadh Al-Sidairi (Sultan Qaboos University Journal for Science, 2002)
Strength development of lime-pozzolana mortars is affected by the fineness of the pozzolan. This paper examines the effect of the fineness of artificial pozzolana on the strength development of lime-pozzolana mixtures. An artificial pozzolana produced by calcining clays from Oman was used in this study. The artificial pozzolana is locally known as “Sarooj”, and is currently being used in a big project for the restoration of historical monuments undertaken by the Omani Ministry of National Heritage and Culture. The artificial pozzolana was ground to various degrees of fineness, blended with hydrated lime with a ratio of 3:1, and the resulting mortar was used to make hardened mortar cubes. Strength of mortar cubes was measured at ages of 7, 14, 28 and 90 days of casting. The experimental results show that good artificial pozzolanas show a linear correlation between the Blaine fineness of the artificial pozzolana and the compressive strength, but such relationship does not exists for weak type pozzolanas. The fineness of the artificial pozzolana has its most significant effect on delayed strength gain, with more pronounced effect for good type pozzolan.